Food insecurity in South Africa: Evidence from NIDS-CRAM wave 5. Issue 5 (3rd September 2022) - van der Berg, Servaas; Patel, Leila; Bridgman, Grace
ABSTRACT: This article presents the results of the five waves of the National Income Dynamics Study – Coronavirus Rapid Mobile Survey (NIDS-CRAM) on food security between May 2020 and May 2021. Despite significant investments in social protection, food insecurity and household and child hunger remained stubbornly high. We conclude that given the protracted nature of the pandemic, slow economic recovery, household and child hunger have stabilised at higher levels than before the pandemic. The phasing out of emergency relief coupled with the constrained economic situation, are some of the reasons why levels of food insecurity and hunger are likely to remain high in the near future. Strict lockdown regulations also reduced employment and income from informal economic activities. Social support for vulnerable individuals and households remain an urgent priority. Continuing support targeted at households with children is particularly important given the dire consequences of enduring hunger for stunting, and on children's long-term development.